2017
DOI: 10.21608/ejar.2017.148768
|View full text |Cite
|
Sign up to set email alerts
|

Partial Substitution of Non-Fat Milk Solids With Dehulled Black Rice Flour in Ice Milk Manufacture

Abstract: he current study was carried out to investigate some quality attributes of ice milk prepared from dehulled black rice flour. Dehulled black rice flour used as a partial substitute of skim milk powder (SMP) at ratios of zero (control), 25, 50, 75 and 100% and as a stabilizer in ice milk mixes. The chemical, physical, and rheological properties as well as sensory attributes of resultant ice milk samples were studied. Results showed that, substitution of SMP with dehulled black rice flour was significantly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Likewise, this phenomenon may be ascribed also to the use of pomegranate peel powdered extract (PPPE) were replacement in a study on pomegranate peel powdered extract (PPPE) versus pectin gelatinize. The results an in same manner with Tawfek et al (2017) who found an increase in viscosity of ice milk mixes with adding dehulled black rice flour. With respect to the freezing point (FP), data demonstrated that, the fat replacement led to lower the FP of the frozen yoghurt mix (Table4).…”
Section: Physical and Rheological Properties Of Frozen Yoghurt MIXsupporting
confidence: 84%
See 2 more Smart Citations
“…Likewise, this phenomenon may be ascribed also to the use of pomegranate peel powdered extract (PPPE) were replacement in a study on pomegranate peel powdered extract (PPPE) versus pectin gelatinize. The results an in same manner with Tawfek et al (2017) who found an increase in viscosity of ice milk mixes with adding dehulled black rice flour. With respect to the freezing point (FP), data demonstrated that, the fat replacement led to lower the FP of the frozen yoghurt mix (Table4).…”
Section: Physical and Rheological Properties Of Frozen Yoghurt MIXsupporting
confidence: 84%
“…Moreover, the FP of frozen yoghurt mixes is highly dependent directly on, the soluble components like sweeteners and indirectly to, the ratio of fat and protein in the frozen yoghurt mix. FP of frozen yoghurt mixes was significantly affected with adding pomegranate peel powdered extract (PPPE).The Obtained results are in line with Tawfek et al (2017). Furthermore, the results indicated also that, as the acid produced by ordinary versus bio BSC was high the FP of the related frozen yoghurt mix was low.…”
Section: Physical and Rheological Properties Of Frozen Yoghurt MIXsupporting
confidence: 66%
See 1 more Smart Citation